Immunity to Visceral Leishmaniasis Using Genetically Defined Live-Attenuated Parasites - Angamuthu Selvapandiyan; Ranadhir Dey; Sreenivas Gannavaram; Ines Lakhal-Naouar; Robert Duncan; Poonam Salotra; Hira L. Nakhasi (Journal of Tropical Medicine)
Leishmaniasis is a protozoan parasitic disease endemic to the tropical and subtropical regions of the world, with three major clinical forms, self-healing cutaneous leishmaniasis (CL), mucocutaneous leishmaniasis (MCL), and visceral leishmaniasis (VL). Drug treatments are expensive and often result in the development of drug resistance. No vaccine is available against leishmaniasis. Subunit Leishmania vaccine immunization in animal models has shown some efficacy but little or none in humans. However, individuals who recover from natural infection are protected from reinfection and develop life-long protection, suggesting that infection may be a prerequisite for immunological memory. Thus, genetically altered live-attenuated parasites with controlled infectivity could achieve such memory. In this paper, we discuss development and characteristics of genetically altered, live-attenuated Leishmania donovani parasites and their possible use as vaccine candidates against VL. In addition, we discuss the challenges and other considerations in the use of live-attenuated parasites.